Pharmacological targeting of GLI1 inhibits proliferation, tumor emboli formation and in vivo tumor growth of inflammatory breast cancer cells. (28th December 2017) - Oladapo, Helen O.; Tarpley, Michael; Sauer, Scott J.; Addo, Kezia A.; Ingram, Shalonda M.; Strepay, Dillon; Ehe, Ben K.; Chdid, Lhoucine; Trinkler, Michael; Roques, Jose R.; Darr, David B.; Fleming, Jodie M.; et al.
Abstract: Activation of the Hedgehog (Hh) pathway effector GLI1 is linked to tumorigenesis and invasiveness in a number of cancers, with targeting of GLI1 by small molecule antagonists shown to be effective. We profiled a collection of GLI antagonists possessing distinct mechanisms of action for efficacy in phenotypic models of inflammatory and non-inflammatory breast cancer (IBC and non-IBC) that we showed expressed varying levels of Hh pathway mediators. Compounds GANT61, HPI-1, and JK184 decreased cell proliferation, inhibited GLI1 mRNA expression and decreased the number of colonies formed in TN-IBC (SUM149) and TNBC (MDA-MB-231 and SUM159) cell lines. In addition, GANT61 and JK184 significantly down-regulated GLI1 targets that regulate cell cycle (cyclin D and E) and apoptosis (Bcl2). GANT61 reduced SUM149 spheroid growth and emboli formation, and in orthotopic SUM149 tumor models significantly decreased tumor growth. We successfully utilized phenotypic profiling to identify a subset of GLI1 antagonists that were prioritized for testing in in vivo models. Our results indicated that GLI1 activation in TN-IBC as in TNBC, plays a vital role in promoting cell proliferation, motility, tumor growth, and formation of tumor emboli. Highlights: TN-IBC (SUM149) and TNBC (SUM159) cell lines expressed elevated levels of GLI1. GANT61 and JK184 inhibited proliferation and colony formation of SUM149/159 and MDA-MB-231. GANT61 and JK184 reduced expression of GLI1 and genes involved in cell cycle progression. In 3D models of SUM149 and SUM159, GANT61 reduced tumor spheroid size and tumor emboli formation. GANT61 had significant in vivo efficacy in orthotropic xenograft models for IBC.